Acute coronary syndrome: pre-hospital lethality structure - Ya. L. Gabinsky; A. A. Grishina (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To study gender-specific pre-hospital lethality structure in acute coronary syndrome (ACS); to identify prognostic factors. Material and methods. The study included 531 patients with acute myocardial ischemia and various pre-hospital outcomes. Statistical analysis of clinical data was performed, using c_2 correlation and regression methods. Results. Pre-hospital death risk was higher in males over 60 years, females over 80 years, in patients with atypical ACS clinics, with symptom onset and ambulance call time from 21.00 to 09.00, in individuals not receiving specialist care or with no previous ambulatory follow-up. Conclusion. Pre-hospital death risk in ACS could be affected by biological, chrono-biological, organizational factors, individual clinical features, patient’s contact with healthcare providers. Some signs of gender dimorphism were observed.